Forced nest site relocations negatively affect reproductive investment in a colonial seabird species. (June 2020) - Salas, Reyes; Müller, Wendt; Vercruijsse, Harry; Lens, Luc; Stienen, Eric
Abstract: Species breeding in urban environments are highly prone to a wide variety of non-natural, human activities, which range from short-term disturbances to the degradation or loss of suitable habitat. The latter in turn may force individuals to relocate to new sites for foraging or breeding, both of which presumably entails fitness costs due the trade-offs of finding and exploring new habitats. Species showing a high level of spatial foraging specialisation or nest site fidelity are expected to be most vulnerable. In this study, we explored the consequences of nest site loss on the reproductive investment of lesser black-backed gulls ( Larus fuscus ), a site faithful seabird species breeding in an urban environment. We monitored a population of 1.173 colour-ringed gulls across 13 years, that involved several episodes of spatially restricted loss of breeding habitat. We found that birds which lost their breeding territories reduced their investment into the eggs as reflected in a decrease of the clutch volume. They relocated over larger distances compared to birds that relocated voluntarily. Moreover, the likelihood of skipping the subsequent breeding season increased after a forced relocation. These negative effects of forced relocation likely contribute to the decline in the number of breeding pairs in our urban population as observed during the last ten years, and highlights the importance of maintaining a stable breeding environment in urban areas for the conservation of this and potentially other colonial breeding seabird species. Highlights: Urban environments may act as ecological traps for colonial breeding birds. Recurring habitat loss forces animals to relocate nest sites frequently. We show that birds losing their nest sites reduced their reproductive investment. Forced relocations have an as yet underestimated impact on population dynamics.